Effect of Dietary supplementation of Garlic (Allium sativum) oil on the Growth Performance, Carcass Quality and Cost Implication of Broiler Chickens - Oluwafemi R.A; Bamigboye Samson. O; Agbonika D.A; Maduekwe, Innocent. M (Research Parks Publishing LLC, 2020)
This experiment was carried to evaluate the “Effect of dietary supplementation of Garlic (Allium sativum) oil on carcass quality, growth performance and cost implication of broiler chickens”. A total of 180 day–old- (Arboacre) broiler chicks of mixed sex was used in this study which lasted for eight (8) weeks. The birds were divided into four experimental groups; each group was further subdivided into three replicates of fifteen birds per each in a Complete Randomized Design (CRD). The birds were fed on two basal diets (Starter and finisher) throughout the experimental period. The garlic oil (Allum sativum) was added to the basal diet at (0.00, 0.1, 0.2, 0.3%) level respectively. The treatments were T1, T2, T3, and T4 with T1 serving as control. Growth performance, carcass characteristics, and cost implication were recorded. At the end of the experiment, the birds were slaughtered, dressed to estimate the different parameters. The result showed that the diet with 0.3% garlic oil inclusion had significantly (P<0.5) higher body weight and best dressing percentage compared with the control treatment (0. 0%).Garlic oil inclusion reduced the mortality rate of the birds as well as productivity. The results on cost implication of the experiment diets indicated that, the diet with 0.3% level of garlic oil has the highest profitability ratio as compared to other treatment groups. This is be due to the higher weight gains recorded by the group of chicken.